Cep63 recruits Cdk1 to the centrosome: implications for regulation of mitotic entry, centrosome amplification, and genome maintenance - Löffler, Harald; Fechter, Anne; Matuszewska, Marc; Saffrich, Rainer; Mistrik, Martin; Marhold, Joachim; Hornung, Christin; Westermann, Frank; Bartek, Jiri; Krämer, Alwin (Cancer research, 2011)
The discovery how Cdk1 kinase is recruited to centrosomes advances understanding of how mitosis is controlled and why centrosome amplification and chromosomal breakage occur so commonly in cancer cells.
Gesehen am 20.09.2022